Pengaruh Implementasi Nilai-Nilai Kepramukaan terhadap Nilai-Nilai Antikorupsi pada Siswa SMA Islam Sudirman Bruno - Rokhaeni, Een; Karim, Abdul (Faculty of Teacher Training and Education of Undaris, 2023)
Scouting activities have an impact on disciplinary, honest and responsible behavior, but there are still students who lie, arrive late, and don't do assignments, thus requiring the implementation of anti- corruption core values. The aim of the study was to determine the effect of implementing scouting values on anti-corruption values in class X students of SMA Islam Sudirman Bruno, Bruno District, Purworejo Regency. This quantitative study has a population of 103 students, a sample of 27 students with a cluster sampling technique proportional random sampling. Data collection techniques using a questionnaire. After the data collected was analyzed by; normality test, correlation test, regression equation, determination test, and F test. The results showed that after the data was analyzed, the calculated F-test was greater than the F distribution table (93.421 > 3.35), which means that Ho was rejected and Ha was accepted. This means that the more students implement Scouting values, the better the students' anti-corruption core values (discipline, honesty and responsibility), so that Scouting values are not only limited to theory, but are implemented in the daily lives of students who participate in Scouting activities.Keywords: implementation of Scout values, anti-corruption core values